Neutralisation of the interleukin-33/ST2 pathway ameliorates experimental colitis through enhancement of mucosal healing in mice. Issue 12 (21st November 2012) - Sedhom, Mamdouh A K; Pichery, Mélanie; Murdoch, Jenna R; Foligné, Benoit; Ortega, Nathalie; Normand, Sylvain; Mertz, Kirsten; Sanmugalingam, Devika; Brault, Lea; Grandjean, Teddy; Lefrancais, Emma; Fallon, Padraic G; et al.
Abstract : Objective: Inflammatory bowel diseases (IBD) have been intrinsically linked to a deregulated cytokine network, but novel therapeutic principles are urgently needed. Here we identify the interleukin (IL)-33 and its receptor ST2 as key negative regulators of wound healing and permeability in the colon of mice. Design: Expression of IL-33 and ST2 was determined by qRT-PCR, ELISA, immunohistochemistry and western-blot analysis. Wild-type and St2 −/− mice were used in wound healing experiments and in two experimental models of IBD triggered by 2, 4, 6-trinitrobenzene sulphonic acid or dextran sodium sulphate (DSS). Neutralisation of ST2 was performed by using a specific blocking antibody. Results: Nuclear localisation and enhanced expression of IL-33 in myofibroblasts and enterocytes was linked to disease involvement independently of inflammation, while the expression of ST2 was primarily restricted to the colonic epithelia. In two experimental models of IBD, genetic ablation of ST2 significantly improved signs of colitis, while a sustained epithelial expression of the cyto-protective factor connexin-43 was observed in DSS-treated St2 -deficient mice. Unexpectedly, absence of ST2 in non-hematopoietic cells was sufficient to protect against colitis. Consistently, specific inhibition of endogenous ST2-mediated signalling by treatment with neutralising antibody improved DSS-induced colitis. In addition, IL-33 treatment impaired epithelial barrier permeability in vitro and in vivo, whereas absence of ST2 enhanced wound healing response upon acute mechanical injury in the colon. Conclusions: Our study unveiled a novel non-hematopoietic function of IL-33 in epithelial barrier function and wound healing. Therefore, blocking the IL-33/ST2 axis may represent an efficient therapy in IBD.